The Influence Of Motivation, Entrepreneurial Creativity And Business Innovation Towards The Interest Of Generation Z Students In Startup Business In Jember District - Setianingrum, Nurul; Puspitasari, Intan Dwi; Kurniawan, Zulfa Ahmad (Majalah Ilmiah DIAN ILMU, 2024)
Purpose : The development of technology and information is one of the causes of the emergence of creative ideas in business development, one of which is startup businesses. Startup is a new business model that uses technology in its operations. According to MIKTI, the number of Generation Z dominates the average number of startup business employees with a total of 49.60% and founders at 15.20% with details of 80.80% of employees and 53.10% being bachelor's degree graduates. Research purposes. These are: 1. To find out the influence of motivation on generation z students' interest in starting up business in Jember Regency 2. To find out the influence of entrepreneurial creativity on generation z students' interest in starting up business in Jember Regency 3. To find out the influence of business innovation on generation z students' interest in starting up business in Jember Regency 4. To determine the influence of motivation, entrepreneurial creativity and business innovation on generation z students' interest in starting up business in Jember Regency. Research methods: The population used in this research was 1,603 active students at the Faculty of Computer Science, Jember University, with a sample of 102 people. The data collection method uses a questionnaire and data analysis uses multiple linear regression with validity testing, reliability testing, classical assumption testing and hypothesis testing. Research results: temporary assumption that the variables motivation, creativity and business innovation entrepreneurial creativity influence the interest of generation z students in startup business in Jember Regency